A parallel stereovision method used for monitoring the collapse of a three-story frame model subjected to seismic loading - Baohua Shan; Wenting Yuan; Hai Wang; Zhanxuan Zuo (International Journal of Distributed Sensor Networks)
In lab or actual engineering, the traditional contact sensors are always destroyed with damage of structures or models, and this leads to the failure of entire dynamic measurement. To deal with this issue, this article proposes a three-dimensional displacement measurement approach based on the parallel stereovision model. This approach combines the efficient large-scale stereo matching algorithm and the digital image correlation approach to obtain three-dimensional displacement of structural vibration response. In this article, the digital image correlation method is employed to match sequential images of left and right cameras, and the efficient large-scale stereo algorithm is used to obtain the disparity between the left and right images at each moment. Based on the parallel stereovision model, the three-dimensional coordinates of the measured point on the structural surface are achieved accordingly. A shaking table test of a three-story frame model under El Centro earthquake is performed in lab. Experimental results indicate that the displacement curves acquired by the linear variable differential transformers and the proposed method agree well, and this testifies the reliability and effectiveness of the presented approach. Only the presented stereovision approach attains the entire displacement curves of structural collapse when the model collapses, and this demonstrates the capability of the presented stereovision approach monitoring structural collapse.